Quantitative analysis of Upper Miocene Mediterranean reef carbonates: A tool for reconstructing palaeoenvironmental gradients - Giovanni Coletti; Alberto Vimercati; Francesca R. Bosellini; Luca Mariani; Adriano Guido; Alessandro Vescogni; Jesús Reolid; Gerald Auer; Daniela Basso; Alberto Collareta; Giulia Bosio; Or Mordecai Bialik (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

An enigmatic calcified fossil in Middle Triassic strata of the southern Apennines, Italy: form, affinity and facies - Giuseppe Palladino; Adriano Guido; Giacomo Prosser; Stephen Kershaw (Facies, 2026)
An assemblage of dome-shaped calcified fossils was discovered in resedimented deposits of the Monte Facito Formation (Middle Triassic, Ladinian) of the Southern Apennines, Italy. The fossils occur within a mass-transport deposit and are interpreted as having originated in a shallow-marine carbonate environment prior to downslope redeposition. In outcrop, they resemble stromatoporoids or calcareous algae and may have contributed to carbonate substrate development. The fossils consist of successive carbonate laminae separated by micritic to fine-grained carbonate layers. Internally, they display a porous fabric but lack chambers and diagnostic skeletal structures typical of stromatoporoids, other hypercalcified sponges, corals, or calcareous algae. Both the skeletal framework and part of the interlaminar carbonate have undergone extensive neomorphism. Energy Dispersive Spectroscopy analyses indicate a predominantly carbonate composition, whereas the interlaminar material contains Al and Si, suggesting a siliciclastic component. Cathodoluminescence analyses provided no significant additional information. Microbial crusts and possible bioerosional borings locally truncate both skeletal laminae and encrusting microbial fabrics. These features suggest post-mortem colonization by boring organisms, possibly including endolithic sponges, indicating prolonged exposure of the fossils on the seafloor before burial. The affinity of these enigmatic fossils remains unresolved, with hypercalcified sponges and calcareous algae representing the most plausible alternatives. Nevertheless, the associated microbial and bioerosional features indicate participation in a complex microbial/metazoan community that contributed to carbonate substrate production and ecological recovery during the rebuilding of shallow-marine ecosystems following the end-Permian mass extinction.

Serpulid build-up from Miocene last tropical ecosystems in SE Sicily - Rossana Sanfilippo; Mara Cipriani; Emanuela Di Martino; Gemma Donato; Giuseppe Maruca; Gianmarco Minniti; Antonietta Rosso; Adriano Guido (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Preservation of ephemeral microbial fabrics: late Messinian filamentous dendrolites from the Salento Peninsula (central Mediterranean) - Alessandro Vescogni; Adriano Guido (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Mentalis, DAO, and Platysma Muscles Treatment Using Botulinumtoxin A: A Multidisciplinary Italian Consensus Based on Literature Review - Salvatore Piero Fundarò; Giovanni Brunelli; Maria Cazzulani; Guido Dalla Costa; Roberto Dell’Avanzato; Roberta D’Emilio; Carlo Di Gregorio; Antonella Franceschelli; Paola Molinari; Monica Renga; Giovanni Salti; Adriano Santorelli; et al. (Toxicon, 2026)

A thousand-year journey of lithification: CT-analysis and radiocarbon dating of algal reef from Central Mediterranean - Pietro Bazzicalupo; Valentina Alice Bracchi; Mara Cipriani; Adriano Guido; Antonietta Rosso; Rossana Sanfilippo; Francesco Maspero; Anna Galli; Elena de Ponti; Daniela Basso (Marine Geology, 2025)

Mapping benthic marine habitats featuring coralligenous bioconstructions: a new approach to support geobiological research - Giuseppe Maruca; Mara Cipriani; Rocco Dominici; Gianpietro Imbrogno; Giovanni Vespasiano; Carmine Apollaro; Francesco Perri; Fabio Bruno; Antonio Lagudi; Umberto Severino; Valentina A. Bracchi; Daniela Basso; et al. (Ocean Science, 2025)
Seabed mapping represents a very useful tool for seascape characterization and benthic habitat study and requires advanced technologies for acquiring, processing, and interpreting remote data. Particularly, acoustic instruments, such as high-resolution swath bathymetry sounders (i.e., multibeam echosounder: MBES), allow us to recognize, identify, and map the extension of benthic habitats without applying invasive mechanical procedures. Bathymetry and backscatter (BS) data are crucial to perform modern habitat mapping. Although the acquisition and processing of bathymetric data follow standardized procedure (e.g., Hydrographic Organization guidelines), and recent studies have proposed recommendations for backscatter acquisition and processing, a broadly validated methodological approach, integrating geomorphometric analysis for benthic habitat mapping, is still lacking. In this work, a new approach for benthic habitat mapping, with a focus on coralligenous bioconstructions, was developed using the open-source software QGIS. This methodology, tested within the Isola Capo Rizzuto Marine Protected Area (Calabria, Italy), is designed to be freely reproducible by researchers working in the field of marine ecosystem monitoring and conservation. Through the proposed mapping procedure, it is possible to (i) identify benthic habitats in selected study areas by combining bathymetry and BS data with geomorphological indices performed in QGIS and (ii) quantitatively define the 2D and 3D distribution of coralligenous bioconstructions in terms of surface covered, thickness, and volume. Moreover, the statistical analysis of quantitative morphometric data allowed for comparison of geometric characteristics of different coralligenous morphotypes. The obtained results, combined with improvement of minimally invasive sampling and geobiological–geochemical characterization, can contribute to the development of protocols aimed at monitoring marine bioconstructed ecosystems, many of which are protected by national and international regulations due to their importance for Mediterranean biodiversity preservation, and plan actions for their protection and persistence.

Mollusk diversity of coralligenous build-ups in the southwestern Ionian Sea - VALENTINA ALICE BRACCHI; MAURO PIETRO NEGRI; PIETRO BAZZICALUPO; MARCO BERTOLINO; MARA CIPRIANI; GEMMA DONATO; ADRIANO GUIDO; ANTONIETTA ROSSO; ROSSANA SANFILIPPO; FRANCESCO SCIUTO; DANIELA BASSO (Mediterranean Marine Science, 2025)
The coralligenous algal reefs are priority ecosystems of the Circalittoral zone of the Mediterranean Sea shelves. Characterized by decimeter- to meter-high build-ups, these reefs create a complex environment hosting high biodiversity. Despite their common occurrence, the roles of mollusks within coralligenous structures have been overlooked until recently. To address this gap, the CRESCIBLUREEF project investigated samples of coralligenous build-ups collected from diverse settings at similar depths (33.5- 37.2 m) along the SE Sicilian shelf (Italy). In the studied samples, we identified 158 mollusk species –mostly autochthonous– including some previously undocumented for this habitat. Our study underscores the importance of using appropriate sampling techniques in studying mollusk biodiversity and the pivotal role algal reefs play in supporting a diverse array of mollusk species, spanning not only those associated with hard substrates but also epiphytic, cryptic, and infaunal species. Despite the samples being sourced at similar depths, multivariate statistical analysis based on mollusk abundance indicated a distinction between coralligenous morphologies in the living assemblage. Overall, our findings contribute to improving the knowledge on mollusks associated with coralligenous reefs and emphasize the valuable role of mollusks as sensitive indicators of environmental conditions, confirming their vital importance in conservation science and benthic ecology.

Biodiversity associated with a coralligenous build-up off Sicily (Ionian Sea) - Gemma Donato; Rossana Sanfilippo; Daniela Basso; Pietro Bazzicalupo; Marco Bertolino; Valentina Alice Bracchi; Mara Cipriani; Francesco D’Alpa; Adriano Guido; Mauro Pietro Negri; Francesco Sciuto; Donatella Serio; et al. (Regional Studies in Marine Science, 2024)

Microbial consortium involved in ferromanganese and francolite biomineralization in an anchialine environment (Zinzulùsa Cave, Castro, Italy) - Adriano Guido; Matteo Calcagnile; Adelfia Talà; Salvatore Maurizio Tredici; Genuario Belmonte; Pietro Alifano (Science of The Total Environment, 2024)

Hydrogeochemical and isotopic characterization of the main karst aquifers of the middle Valseriana (Northern Italy): Nossana and Ponte del Costone springs - Andrea Citrini; Adriano Mayer; Corrado A.S. Camera; Anita Erőss; Jürgen Sültenfuß; Guido Pezzera; Giovanni Pietro Beretta (Applied Geochemistry, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Geochemical and mineralogical proxies from the Messinian mudrocks (Catanzaro Basin, southern Italy): Paleoweathering and paleoclimate evolution during the onset of the Messinian salinity Crisis - Francesco Perri; Adriano Guido; Mara Cipriani; Giuseppe Cianflone; Rocco Dominici (Marine and Petroleum Geology, 2024)

Double-phased controlled and influenced biomineralization in marine invertebrates: The example of Miocene to recent reef-building polychaete cirratulids from southern Peru - Adriano Guido; Francesco D'Amico; Thomas J. DeVries; Tomáš Kočí; Alberto Collareta; Giulia Bosio; Rossana Sanfilippo (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

A multidisciplinary geochemical approach to geothermal resource exploration: The Spezzano Albanese thermal system, southern Italy - Giovanni Vespasiano; Luigi Marini; Francesco Muto; Luis F. Auqué; Rosanna De Rosa; Jon Jiménez; Maria J. Gimeno; Luca Pizzino; Alessandra Sciarra; Giuseppe Cianflone; Mara Cipriani; Adriano Guido; et al. (Marine and Petroleum Geology, 2023)

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Reconstruction of tectonically disrupted carbonates through quantitative microfacies analyses: an example from the Middle Triassic of Southern Italy - Adriano Guido; Giuseppe Palladino; Matteo Sposato; Franco Russo; Giacomo Prosser; Mario Bentivenga; Adelaide Mastandrea (Facies, 2021)
The main goal of the paper is the reconstruction of a Middle Triassic buildup cropping out in the central part of the Southern Apennines. Middle Triassic reefs of the western Tethys realm are well known in the Northern and Southern Alps. In contrast, few studies of the Anisian–Ladinian carbonate platforms of the southern Apennines are available, due to the diagenetic alteration and tectonic disruption that hinder their paleoenvironmental and stratigraphic reconstruction. In an attempt to fill this gap, and to improve the knowledge on the Anisian–Ladinian carbonates of central Mediterranean area, this research is focused on a carbonate buildup cropping out in the “La Cerchiara” area, Sasso di Castalda (Basilicata, Southern Italy). The buildup, affected by intense tectonic deformation associated with the development of the Apennine thrust and fold belt, was studied using a statistical evaluation of the quantitative microfacies data. The research enabled a reconstruction of the original stratigraphic relationships of the various buildup fragments. A positive linear regression between the sample positions vs the percentage of autochthonous carbonates indicates an increase of the autochthons carbonate toward the top of the succession. The allochthonous fabrics (packstone/wackestone) at the base of the section (Unit IIIa) pass gradually upward into autochthonous (boundstones) facies (Units IIIb, I), consisting of microbialites (clotted peloidal micrite, microbial-derived laminae, and aphanitic micrite), microproblematica and cyanobacterial crusts, with few encrusting skeletal organisms. Statistical data suggest that units IIIa, IIIb, and I are in stratigraphic order while unit II appears to have been moved by tectonic dislocation from its original position at the base of the succession. The absence of metazoan reef framework, and the richness of micro-encrusters, autochthonous micrite and synsedimentary cements, suggest a mud-mound style of growth for the carbonate bodies of the Southern Apennine during the Anisian.

Colonisers of the dark: biostalactite‐associated metazoans from “lu Lampiùne” submarine cave (Apulia, Mediterranean Sea) - Antonietta Rosso; Rossana Sanfilippo; Adriano Guido; Vasilis Gerovasileiou; Emma Taddei Ruggiero; Genuario Belmonte (Marine Ecology, 2021)
Metazoan/microbial bioconstructions, or biostalactites (BSTs), discovered in submarine caves of Apulia c . 20 years ago—and later found in several shallow‐water Mediterranean caves—are receiving increasing attention in the last years. Examination of a single BST from the “lu Lampiùne” cave (Apulia), at the limit between the Adriatic and the Ionian seas, has been addressed for the first time in this paper. The BST started growing at c . 6,000 years ago with a rapid accretion of large‐sized serpulids ( Protula ), slowing down since about 3,000–4,000 years ago with a shift in main bioconstructors, probably caused by environmental changes. The present‐day community on the outer BST surface is dominated by skeletonised epibionts, mostly small‐sized serpulids, bryozoans and foraminifers, which contribute carbonate to the BST growth, by encrusting sponges, and by a few endobionts, including boring bivalves and insinuating sponges. New data remarkably increase biodiversity known for the “lu Lampiùne” cave and the cave habitat in the region. Thirty‐five taxa (16 bryozoans, 10 serpulids, 3 brachiopods, 2 foraminifers, 2 sponges, 1 bivalve and 1 cirriped) are recorded for the first time from Apulian marine caves, highlighting the need for further research in the area. In addition, the BST‐associated community seems to differ from those of individual BSTs from other Mediterranean caves, revealing the individuality of these communities.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Plant–environment interactions through a functional traits perspective: a review of Italian studies - Stefano Chelli; Michela Marignani; Elena Barni; Alessandro Petraglia; Giacomo Puglielli; Camilla Wellstein; Alicia T. R. Acosta; Rossano Bolpagni; Luca Bragazza; Giandiego Campetella; Alessandro Chiarucci; Luisa Conti; et al. (Plant Biosystems, 2019)

Bryozoan assemblages from two submarine caves in the Aegean Sea (Eastern Mediterranean) - Antonietta Rosso; Vasilis Gerovasileiou; Rossana Sanfilippo; Adriano Guido (Marine Biodiversity, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Cryptic serpulid-microbialite bioconstructions in the Kakoskali submarine cave (Cyprus, Eastern Mediterranean) - Adriano Guido; Carlos Jimenez; Katerina Achilleos; Antonietta Rosso; Rossana Sanfilippo; Louis Hadjioannou; Antonis Petrou; Franco Russo; Adelaide Mastandrea (Facies, 2017)

Morphological and mineralogical evolution of microfossils during the heating process: a contribution to the archaeometric study of ceramics - Antonella Privitera; Adriano Guido; Adelaide Mastandrea; Anna Rao; Franco Russo (Rendiconti Lincei. Scienze Fisiche e Naturali, 2015)

Metazoan/microbial biostalactites from present‐day submarine caves in the Mediterranean Sea - Rossana Sanfilippo; Antonietta Rosso; Adriano Guido; Adelaide Mastandrea; Franco Russo; Robert Riding; Emma Taddei Ruggiero (Marine Ecology, 2015)
Biostalactites formed by metazoan – microbialite associations from three submerged marine caves in the Plemmirio Peninsula (south of Syracuse, Ionian Sea) are randomly distributed and show different sizes and morphologies, as well as variations in surface roughness/smoothness. The biostalactites consist of crusts a few centimeters thick of small serpulids and other metazoans, associated with fine‐grained carbonate; the larger ones often include a nucleus of serpulid tubes ( Protula ). The metazoans include mainly serpuloideans, sponges, bryozoans and foraminifers but microbial carbonates are also significant components. The composition of both the living communities and thanatocoenoses on the outer surfaces, as well as the composition and fabric of the internal framework, were analysed and used to reconstruct the history of the caves. All of the identified sessile faunas mainly consist of cryptic and sciaphilic dwellers that reflect cave conditions and their variations through time. The distribution pattern, composition and abundance of the present‐day dwellers largely depend on the degree of roughness of the biostalactite surfaces and their positions within the caves. It has been suggested that the Protula specimens in the nuclei represent pioneer populations that formed aggregates during the early cave colonization phase, in response to relatively high food supply from seawater inflow and intruding continental waters. By contrast, the outer metazoan–microbialite carbonates reflect more confined conditions in the caves caused by Holocene sea‐level rises. Hypotheses are proposed for biostalactite growth, taking into account information about the growth rates of some constituents, and evidence of dissolution effects. Similarities and differences between these biostalactites and other Holocene deposits previously described from submarine caves in the Mediterranean Sea and in tropical reefs are discussed.

Micromorphological, geochemical, and diagenetic characterization of sirenian ribs preserved in the Late Miocene paleontological site of Cessaniti (southern Calabria, Italy) - Adriano Guido; Antonella Cinzia Marra; Adelaide Mastandrea; Fabio Tosti; Franco Russo (Facies, 2012)

The effects of seed availability on habitat use by a specialist seed predator - Erica Di Pierro; Anne Ghisla; Lucas A. Wauters; Ambrogio Molinari; Adriano Martinoli; John Gurnell; Guido Tosi (European Journal of Wildlife Research, 2011)

Space use patterns of mountain hare (Lepus timidus) on the Alps - Francesco Bisi; Mosé Nodari; Nuno Miguel Dos Santos Oliveira; Elisa Masseroni; Damiano G. Preatoni; Lucas A. Wauters; Guido Tosi; Adriano Martinoli (European Journal of Wildlife Research, 2011)

Rare earth element signatures in the Messinian pre-evaporitic Calcare di Base formation (Northern Calabria, Italy): evidence of normal seawater deposition - Adelaide Mastandrea; Donatella Barca; Adriano Guido; Fabio Tosti; Franco Russo (Carbonates and Evaporites, 2010)

From mass of body elements to fish biomass: a direct method to quantify food intake of fish eating birds - Alessandra Gagliardi; Adriano Martinoli; Damiano Preatoni; Luc A. Wauters; Guido Tosi (Hydrobiologia, 2007)

Modelling the Expansion of a Grey Squirrel population: Implications for Squirrel Control - Clara Tattoni; Damiano G. Preatoni; Peter W. W. Lurz; Steven P. Rushton; Guido Tosi; Sandro Bertolino; Adriano Martinoli; Lucas A. Wauters (Biological Invasions, 2006)

Species Richness and Habitat Use of Small Carnivores in the Arusha National Park (Tanzania) - Adriano Martinoli; Damiano Preatoni; Valeria Galanti; Paola Codipietro; Morris Kilewo; Carlos A. R. Fernandes; Luc A. Wauters; Guido Tosi (Biodiversity and Conservation, 2006)

Interspecific competition between native Eurasian red squirrels and alien grey squirrels: does resource partitioning occur? - Luc Wauters; John Gurnell; Adriano Martinoli; Guido Tosi (Behavioral Ecology and Sociobiology, 2002)